Newfoundland and Labrador: Provincial Policing and Federal Youth Justice Legislation - Carbonell, Marina; Ricciardelli, Rosemary (Newfoundland and Labrador Studies)

(untitled) (Faculty of Arts, Memorial University, 2022)
In Canada, the practical application of youth diversion is rooted in an understanding of federal youth justice legislation and requires the consideration of police discretion. Yet, policing in Newfoundland and Labrador is shaped by localized practices, policies, and decisions. In the current article, we draw on online survey data to explore how Royal Newfoundland Constabulary (RNC) officers understand and apply Canada’s current federal youth legislation — the Youth Criminal Justice Act (YCJA) — and identify what factors, if any, influence the YCJA’s application. To unpack police officer attitudes towards youth and the YCJA and the actions police choose when handling matters involving youth, we draw from data collected from non-commissioned officers working in one of the three RNC detachments in 2016. Findings show that officers perceive a lack of YCJA resources available to front-line police officers in urban centres and a need for further training for officers who interact with youth. A desire for youth diversion services was evident among participants; however, the lack of availability of police-accessible pre-charge diversion options in Newfoundland and Labra-dor, including specific programs for youth, as well as police-specific training, are primary influencing factors affecting the understanding, implementation, and success of youth diversion in the province.